Cytokine responses to novel antigens in an Indian population living in an area endemic for visceral leishmaniasis. - Om Prakash Singh; Carmel B Stober; Abhishek Kr Singh; Jenefer M Blackwell; Shyam Sundar (Public Library of Science (PLoS), 2012)
There are no effective vaccines for visceral leishmaniasis (VL), a neglected parasitic disease second only to malaria in global mortality. We previously identified 14 protective candidates in a screen of 100 Leishmania antigens as DNA vaccines in mice. Here we employ whole blood assays to evaluate human cytokine responses to 11 of these antigens, in comparison to known defined and crude antigen preparations.Whole blood assays were employed to measure IFN-γ, TNF-α and IL-10 responses to peptide pools of the novel antigens R71, Q51, L37, N52, L302.06, J89, M18, J41, M22, M63, M57, as well as to recombinant proteins of tryparedoxin peroxidase (TRYP), Leishmania homolog of the receptor for activated C kinase (LACK) and to crude soluble Leishmania antigen (SLA), in Indian patients with active (n = 8) or cured (n = 16) VL, and in modified Quantiferon positive (EHC(+ve), n = 20) or modified Quantiferon negative (EHC(-ve), n = 9) endemic healthy controls (EHC).Active VL, cured VL and EHC(+ve) groups showed elevated SLA-specific IFN-γ, but only active VL patients produced IL-10 and EHC(+ve) did not make TNF-α. IFN-γ to IL-10 and TNF-α to IL-10 ratios in response to TRYP and LACK antigens were higher in cured VL and EHC(+ve) exposed individuals compared to active VL. Five of the eleven novel candidates (R71, L37, N52, J41, and M22) elicited IFN-γ and TNF-α, but not IL-10, responses in cured VL (55-87.5% responders) and EHC(+ve) (40-65% responders) subjects.Our results are consistent with an important balance between pro-inflammatory IFNγ and TNFγ cytokine responses and anti-inflammatory IL-10 in determining outcome of VL in India, as highlighted by response to both crude and defined protein antigens. Importantly, cured VL patients and endemic Quantiferon positive individuals recognise 5 novel vaccine candidate antigens, confirming our recent data for L. chagasi in Brazil, and their potential as cross-species vaccine candidates.